Strategi Pemasaran Produk UMKM Melalui Penerapan Digital Marketing - Azmi Fadhilah, Dian; Pratiwi, Tami (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
The scientific paper of Product Marketing Strategy of Micro, Small, and Medium Enterprise (MSME) Through the Application of Digital Marketing is aims to discover the impact of digital marketing on the sale of MSME products, by comparing MSME that used digital marketing as a means of promotion and product sales with MSME that haven’t used the digital marketing, and to discover how to implement of digital marketing efforts to MSME in Cibunar Village, Rancakalong. In writing this scientific paper, the research method used is descriptive qualitative research. The research subject in this research are informants who provide research data through interviews and through purposive sampling technique. Based on the result of qualitative research with interview and observation techniques as well as the data that has been collected by the author, it can be concluded that digital marketing has a huge influence on product marketing because it can increase the sales volume and also increase the profits for MSME entrepreneurs.